Geneza i rozwój osad hutniczych w Borach Dolnośląskich (XIV-XIX w.) = Genesis and development of steelworks colony in Bory Dolnośląskie (XIV-XIX centuries) - Krajniak, Wiktor (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the history of steelworks colony in Bory Dolnośląskie. The author discussed their genesis and further history in XIV-XIX centuries. The conditions of metallurgical development in the realities of feudal, grange-serfdom and capitalist economy were analyzed.
Keywords: Dolny Śląsk; Bory Dolnośląskie; hutnictwo; kuźnice; ruda darniowa; żelazo; Lower Silesia; iron; iron mill; iron ore; metallurgy